Tests of Attention in Newly Diagnosed Idiopathic Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs)
Performance on tests of Reaction Time, Color Trails, Manual Tapping and Steadiness, and Sustained Attention were compared in 51 children with epilepsy (age 7-16 years) and 48 healthy classmates, in a study at Wilhelmina Children’s Hospital, Utrecht, the Netherlands.